Systematic Literature Review: Peran Authentic Leadership Dalam Industri Penerbangan - Toding, Bernard Irianto; Rany Adiliawijaya Putriekapuja (Jurnal Bisnis dan Operasi Penerbangan, 2024)
Aviation transportation plays a vital role in supporting economic activity, tourism and international human mobility. However, the industry faces various challenges, including management problems and conflicts with customers. Authentic leadership is considered capable of overcoming this challenge by creating a positive work culture and increasing customer satisfaction. This research aims to understand the influence of authentic leadership in the aviation transportation industry through the Systematic Literature Review (SLR) method. A literature search was carried out using Google Scholar with related keywords and produced 18 potential journals which were then selected into 6 high quality journals. The research results show that authentic leadership has a significant effect on work culture, employee motivation and customer satisfaction. Authentic leadership drives employee trust and engagement, which in turn improves the quality of service and operational performance of airlines. This research provides important insights for practitioners and academics in developing authentic leadership to increase management effectiveness and operational success in the aviation industry.